Analisis Praanggapan Dalam Video “Eksklusif: Ganjar Pranowo Dan Piala Dunia” Pada Wawancara Mata Najwa - Kerin Theresa Saragih; Lasenna Siallagan; William Sitorus; Dinda Anggraini Ginting; Loudwig Agustinus Purba; Mutiara Putrimina (FKIP, Universitas Palangka Raya, 2023)
This study aims to describe the various types of presuppositions contained in the video “Eksklusif: Ganjar Pranowo dan Piala Dunia” in Mata Najwa. This study used qualitative descriptive, namely a study which obtains data by providing an explanation or description of the situation or condition under study in the form of a description. The data in this study were in the form of utterances stated in the video Eksklusif: Ganjar Pranowo dan Piala Dunia” in Mata Najwa. Data were collected by observing and note-taking. Having collected and classified according to the type of presupposition, the data were analyzed using presupposition theory. The results of the study showed that there were 43 presupposition data in the video “Eksklusif: Ganjar Pranowo dan Piala Dunia” in Mata Najwa. The data consist of 17 existential presupposition data, 4 inactive presupposition data, 6 lexical presupposition data, 11 structural presupposition data, 2 non-factive presupposition data and 3 counterfactual presupposition data.